PREOrg : um guia para elicitação de requisitos orientado ao desempenho organizacional - Rebouças, Flaygner Matos (2018)
In the software development cycle, requirements elicitation is one of the first activities to be performed and can be repeated in all other stages of requirements engineering. The Business Analyst needs to understand deeply characteristics of the organization where it operates by understanding business processes and seeking the necessary knowledge to propose intelligent alternatives to the processes. Requirements elicitation techniques help to identify a greater volume of requirements by suggesting that requirements elicitation is performed in a way close to the organization's business processes but do not observe how elicitation of requirements should support the improvement in organizational performance. Interest in this research arose through the concern with evolution and improvements of techniques and methodologies found in the area of requirements engineering, with the challenge and the need to develop systems that truly meet the expectations of stakeholders and that, above all, engagement with business areas of organizations. This research proposes the development of a guide to requirements elicitation oriented to organizational performance. PREOrg is a guide to best practices for elicitation of software requirements oriented to organizational performance that proposes identification of opportunities for generation of results, improvement of processes and support to decision making, from elicitation of software requirements. Two case studies were performed with the objective of proving the eficiency and effectiveness of PREOrg. The first case study was carried out in industry involving software and the second in a public organization involving three softwares in both cases a training was carried out involving systems analysts responsible for eliciting requirements for the construction of the software, in order to provide knowledge of the processes proposed by PREOrg. As a result, evidence was found that PREOrg contributed to definition of requirements capable of supporting development of software oriented to organizational performance. First case study presented evidence of financial improvement for the organization where software was deployed. In the second case study, evidence was found that the use of PREOrg is useful for elicitation of requirements that support the development of software capable of assisting in decision making and improvement of organizational processes.